Hierarchical Relations in Simulation Models - Luna, J.J. (WSC, '93: Winter Simulation Conference Proceedings, 1993)
Hierarchical modeling is a powerful means to handle system simulation model complexity. It can often be loosely defined, however, creating ambiguities in its application to simulation modeling. In order to define hierarchical modeling, different aspects of simulation models are defined. Then four principal model hierarchical relations are defined and discussed: representation, composition, substitution, and specification. Hierarchical relations are then applied to the appropriate model aspects to provide a more complete definition of hierarchical modeling.